2015
DOI: 10.1021/acsami.5b00093
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Domain Short Peptide Molecules for in Situ Synthesis and Biofunctionalization of Gold Nanoparticles for Integrin-Targeted Cell Uptake

Abstract: We describe design and synthesis model of multidomain (modular) peptides (MDPs), which direct a reaction cascade coupling the synthesis and surface functionalization of gold nanoparticles (AuNPs) in a single step. The synthesis is achieved via simple mixing of the aqueous solutions of auric acid and MDPs at room temperature without the addition of any surfactants or toxic intermediate reagents. This method allows facile control over the nanoparticle size between ∼2−15 nm, which opens a practical window for bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…To understand endocytosis and exocytosis behavior, we first investigated the mechanism of AuNPs uptake by HUVECs. Although the uptake mechanisms of bare and surface-functionalized AuNPs in a variety of sizes and shapes have been characterized in the literature, their internalization is difficult to generalize and may depend on processes such as macropinocytosis 37 , phagocytosis 38 39 , receptor mediated endocytosis 7 (clathrin- or caveolae-mediated endocytosis) and transcytosis 40 . Therefore, three of these major pathways (macropinocytosis, caveolae-mediated endocytosis, and clathrin-mediated endocytosis) were blocked by inhibitor treatment to observe whether AuNP uptake depended on any of these mechanisms ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand endocytosis and exocytosis behavior, we first investigated the mechanism of AuNPs uptake by HUVECs. Although the uptake mechanisms of bare and surface-functionalized AuNPs in a variety of sizes and shapes have been characterized in the literature, their internalization is difficult to generalize and may depend on processes such as macropinocytosis 37 , phagocytosis 38 39 , receptor mediated endocytosis 7 (clathrin- or caveolae-mediated endocytosis) and transcytosis 40 . Therefore, three of these major pathways (macropinocytosis, caveolae-mediated endocytosis, and clathrin-mediated endocytosis) were blocked by inhibitor treatment to observe whether AuNP uptake depended on any of these mechanisms ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This result suggests that AuNPs were predominantly entering into HUVECs via macropinocytosis. Gulsuner et al, showed that MDP-AuNPs which contains RGD sequence as targeting moiety enters into breast cancer cells via both clathrin-mediated endocytosis and macropinocytosis pathway 37 . The cells might use non-specific entry routes for endocytosis of non-functionalized AuNPs.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 These molecules, besides being stably adsorbed on the AuNP surfaces, self-assemble and create dense networks of interconnected structures which prevent water from reaching the metal supports. 19,20 Moreover, while the thiol groups form strong bonds with the gold interface and stabilize the substrate, the other portions of the chains are involved in interactions with the surrounding environment (solvent, peptides, proteins, enzymes, lipids, etc.). 21,22 Given these premises, it would be crucial to disclose at the atomic level the behavior of AuNPs in solution when thiolcontaining amino acids (for example cysteine) are adsorbed on their faces and to understand in detail the dynamics of surface functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…The peptides are natural compounds in synthesizing the biocompatible metal nanoparticles in mild conditions [135][136][137][138][139]. They act as reducing agent as well as the capping agent during nanomaterials synthesis.…”
Section: Peptides In Nanoparticle Synthesismentioning
confidence: 99%
“…In another research, Giese et al explained the synthesis of AgNPs under electron transfer conditions [136] where Ag+ ions bound by a histidine as the Ag-binding amino acid and a tyrosine as a photo inducible electron donor of the bound peptide. The application of a multidomain peptide (DOPA) for single-step, size-controlled synthesis of biofunctionalized AuNPs was described by Tekinay and coworkers [137]. The size-controlled synthesis of AuNPs was possible due to the presence of 3,4-dihydroxy-L-phenylalanine (L-DOPA) functional group in the peptide which is reductive in nature.…”
Section: Peptides In Nanoparticle Synthesismentioning
confidence: 99%